Urine‐derived podocytes‐lineage cells: A promising tool for precision medicine in Alport Syndrome. Issue 2 (22nd November 2017) - Daga, Sergio; Baldassarri, Margherita; Lo Rizzo, Caterina; Fallerini, Chiara; Imperatore, Valentina; Longo, Ilaria; Frullanti, Elisa; Landucci, Elisa; Massella, Laura; Pecoraro, Carmine; Garosi, Guido; Ariani, Francesca; et al.
Abstract: Alport Syndrome (ATS) is a rare genetic disorder caused by collagen IV genes mutations, leading to glomerular basement membrane damage up to end‐stage renal disease. Podocytes, the main component of the glomerular structure, are the only cells able to produce all the three collagens IV alpha chains associated with ATS and thus, they are key players in ATS pathogenesis. However, podocytes‐targeted therapeutic strategies have been hampered by the difficulty of non‐invasively isolating them and transcripts‐based diagnostic approaches are complicated by the inaccessibility of other COL4 chains‐expressing cells. We firstly isolated podocyte‐lineage cells from ATS patients' urine samples, in a non‐invasive way. RT‐PCR analysis revealed COL4A3, COL4A4, and COL4A5 expression. Transcripts analysis on RNA extracted from patient's urine derived podocyte‐lineage cells allowed defining the pathogenic role of intronic variants, namely one mutation in COL4A3 (c.3882+5G>A), three mutations in COL4A4 (c.1623+2T>A, c.3699_3706+1del, c.2545+143T>A), and one mutation in COL4A5 (c.3454+2T>C). Therefore, our cellular model represents a novel tool, essential to unequivocally prove the effect of spliceogenic intronic variants on transcripts expressed exclusively at a glomerular level. This process is a key step for providing the patient with a definite molecular diagnosis and with a proper recurrence risk. The established system also opens up the possibility of testing personalized therapeutic approaches on disease‐relevant cells. Abstract : Alport syndrome (ATS) is a rare disorder characterized by a progressive GBM damage due to COL4α chains mutations. Podocytes, the only cells producing the COL4 α3, α4, α5 heterotrimer essential for GBM integrity, are the main determinant of ATS pathogenesis. Notably, we firstly isolated podocytes‐lineage cells from ATS patient's urine samples, and, as proof‐of‐principle, we demonstrated that they represent an innovative tool to characterize COL4 chains intronic variants, in line with a diagnostic and therapeutic precision medicine approach.